2010
DOI: 10.1111/j.1741-1130.2010.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Dementia in Older Adults With Intellectual Disabilities-Epidemiology, Presentation, and Diagnosis

Abstract: Background: As life expectancy of people with intellectual disabilities (ID) extends into older

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 77 publications
2
114
2
3
Order By: Relevance
“…Another feature of AD-DS is the more-frequent and earlier appearance of neurological symptoms such as gait disturbance and seizures 19 when compared with LOAD. Although heterogeneous, seizures associated with AD-DS often initially present with myoclonic jerks before progressing to tonic-clonic seizures and later to non-epileptic myoclonus with cerebellar signs; electroencephalograms show diffuse slowing and spike-and-wave patterns [48][49][50] .…”
Section: Clinical Features Of Ad-dsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another feature of AD-DS is the more-frequent and earlier appearance of neurological symptoms such as gait disturbance and seizures 19 when compared with LOAD. Although heterogeneous, seizures associated with AD-DS often initially present with myoclonic jerks before progressing to tonic-clonic seizures and later to non-epileptic myoclonus with cerebellar signs; electroencephalograms show diffuse slowing and spike-and-wave patterns [48][49][50] .…”
Section: Clinical Features Of Ad-dsmentioning
confidence: 99%
“…As indicated above, AD is now common in adults with DS who are over the age of 40 years and, like other genetic forms of EOAD, develops two to three decades earlier in individuals with DS than in the general population. Data describing the prevalence of AD-DS vary between studies because of diagnostic issues, such as the presence of variable premorbid deficits, and survey methodology 19 . However, the prevalence of AD in people who have DS is <5% under the age of 40 (REF.…”
Section: Prevalence Of Ad-dsmentioning
confidence: 99%
“…Dementia in ID is frequently associated with co-morbidities including psychiatric presentations, for example depression, and behavioral problems (8). Some of these psychiatric co-morbidities including problem behavior may be noted to improve with the prescription of dementia medication listed above.…”
Section: Management Of Behavioral and Psychiatric Symptoms Associatedmentioning
confidence: 99%
“…Nevertheless, there are increasing numbers of older adults with ID who may require considerable care inputs. The average annual cost of care for older individuals with ID in the UK is approaching £50,000 ($71,952; €54,034 at 2013 rates for purchasing power parity), most of which is accounted for by personal care rather than health care costs, with mental health problems being an important predictor of costs) (8). Appropriate treatment and management of behavioral and psychiatric symptoms may therefore help to reduce the burden on caregivers as well as the cost of care.…”
Section: Introductionmentioning
confidence: 99%
“…12 Wiseman et al 13 reported that approximately 5% to 15% of people with DS aged 40 to 49 years and more than 30% of those aged 50 to 59 years experience a significant decline in their cognition, indicating dementia. McCarron et al 14 reported that 68% to 80% of people with DS have developed dementia by the age of 65 years.…”
Section: Introductionmentioning
confidence: 99%